Pedagogical Adaptations of Multigrade Teachers in Implementing the Matatag Curriculum in Pudtol District - Ricardo, Charmaine (Studies in Technology and Education, 2026)
This study examined the pedagogical adaptations of multigrade teachers in implementing the MATATAG Curriculum in Pudtol District during the school year 2025–2026. Using a mixed-method approach, data were gathered from 24 multigrade teachers through a researcher-made questionnaire and semi-structured interviews. Descriptive statistics and thematic analysis were used to analyze the data. Findings revealed that teachers commonly applied pedagogical strategies in teaching delivery and assessment practices, while learning support and remediation were less emphasized. Major challenges included limited instructional materials, heavy workload, inadequate technology access, learners’ difficulties in reading and basic skills, and inconsistent parental support. Support mechanisms were mainly provided by school heads, DepEd training programs, and co-teachers. Best practices identified were peer tutoring, differentiated instruction, integrated lesson planning, structured routines, and parental engagement. The study concluded that multigrade teachers demonstrate adaptive instructional practices, but stronger remediation and support systems are needed to enhance instructional effectiveness under the MATATAG Curriculum.